The Incident of People with Severe Mental Disorders: A 5 Years Epidemiology at Nusa Penida I Public Health Center - Kusuma, I Made Peri Ardiana (E-Jurnal Medika Udayana; Vol 12 No 6 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i06.P13, 2023)
Background: Public Health Center (PHC) is responsible for carrying mental health effort through promotive, preventive, curative and rehabilitative approach. Nusa Penida, an archipelago area included in the Klungkung Regency, has problems in providing advanced (specialist) level health services related to mental health because infrastructure and human resources are not yet available. The aim of this study is to determine the prevalence and characteristic of PWSMD in the NP I PHC area so that it can provide data estimates related to mental health services. Patients and Methods: This study is a retrospective, single-center observational study from 2017 to 2021 with non-probability sampling technique in a consecutive manner. All data was collected and recorded, then processed and displayed in the form of proportion (percentage), sum, mean (standard deviation), and median (minimum-maximum). Results: During the study period from 2017 to 2021, a total of 105,137 patient visits were obtained, with 456 visits being PWMD (0.43%) and 370 visits being PWSMD (0.35%). The proportion of PWSMD from PWMD was 81.1%. Sixty five patients were obtained from the total visits of PWSMD with male and the 26-45 year age group had the highest number of percentage (56.7% and 29.2%). Batununggul Village, which is the closest working area to the NP I PHC, has the highest number of patient visits Conclusion: This study showed that the prevalence of PWSMD in the working area of the NP I Public Health Center was quite high with the majority being diagnosed as paranoid schizophrenia.  Most of the patient visits were from Batununggul village. Keywords: severe mental disorder, public health care, schizophrenia, nusa penida